A study on relationship between workload and stress level among secondary school teachers in Sekolah Menengah Sains Sultan Haji Ahmad Shah and Sekolah Menengah Kebangsaan Tengku Ampuan Afzan Kuantan / Fairuz Safuraa Mohd Sofian - Mohd Sofian, Fairuz Safuraa (2013)
The purpose of this study was to study the relationship between workload and stress level among secondary school teachers. The study focused on secondary school teachers in Sekolah Menengah Sains Sultan Haji Ahmad Shah Kuantan and Sekolah Menengah Kebangsaan Tengku Afzan Kuantan. The questionnaire was used to investigate the relationship workload and stress level among secondary school teacher. The questionnaire was distributed randomly in the secondary schools. The school was selected to provide a relationship to types of workload and stress level due to the workload. The study also wanted to identify whether extreme workload of secondary school teachers contributed to stress level. In this study, the workload was identified into three aspects which were academic, co-curriculum, and special task. There are three aspects of workload that experienced by secondary school teachers caused exhaustion, tension and headache. A stress was the implication that happened due to the extreme workloads. Teachers who faced extreme workloads caused too little time to rest and quality time with family will less and insufficient time to complete their work very well. Apart from that, the study also to identify whether the workloads bring to the percentage of positive and negative stress level among secondary school teachers. On the other hand, the study wanted to analyse the independent variable and dependent variable which were involved workload and stress level.